2022
DOI: 10.1021/acssuschemeng.2c05002
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Nitrogen-Doped Carbon Spheres with Wrinkled Cage-Supported Single-Atom Copper Catalysts for Selective Oxidation of Glycerol to Formic Acid

Abstract: Selective conversion of the surplus glycerol (GLY) to a hydrogen storage material, formic acid (FA), in heterogeneous catalytic systems is still challenging in the catalysis community. Herein, nitrogen-doped carbon spheres with wrinkled cagesupported single-atom Cu catalysts (Cu/NCSWCs) were prepared by wet ball milling of 5,5′-diamino-3,3′-bis(1H-1,2,4-triazole) (DABT) and copper nitrate with hydrothermal carbon-encapsulated dendritic fibrous nanosilica (DFNS) as the hard template in methanol. After the remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The resultant Cu/NCSWCs possessed unique CuN 4 structures and large meso/macropore volumes, leading to a high catalytic activity and selectivity in oxidation of glycerol to formic acid using H 2 O 2 as the oxidant. 208…”
Section: The Roles Of Salt In Carbon Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant Cu/NCSWCs possessed unique CuN 4 structures and large meso/macropore volumes, leading to a high catalytic activity and selectivity in oxidation of glycerol to formic acid using H 2 O 2 as the oxidant. 208…”
Section: The Roles Of Salt In Carbon Synthesismentioning
confidence: 99%
“…The resultant Cu/NCSWCs possessed unique CuN 4 structures and large meso/macropore volumes, leading to a high catalytic activity and selectivity in oxidation of glycerol to formic acid using H 2 O 2 as the oxidant. 208 Bimetallic or alloy systems have been demonstrated to be a family of versatile functional materials in electrocatalysis and energy storage. [209][210][211][212] Wu et al reported Ni-Cu alloy nanoparticles embedded in N-doped porous carbon nanosheets (NiCu@NHPC) using lactose monohydrate as a carbon source and Ni(NO 3 ) 2 •6H 2 O and Cu(NO 3 ) 2 •3H 2 O as the metal source and nitrogen source.…”
Section: As Precursormentioning
confidence: 99%